2004
DOI: 10.2320/matertrans.45.2031
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Al K-edge X-ray Absorption Spectra of Al, AlN and Al<SUB>2</SUB>O<SUB>3</SUB>

Abstract: High-resolution X-ray absorption spectra of Al, AlN and Al 2 O 3 are measured at the Al K-edge, which have revealed a chemical shift in the threshold energy and significant differences in the spectral fine structures among the three compounds. In order to interpret the chemical shift and the fine structures of these spectra, first-principles calculations using the full-potential linearized augmented plane wave method within the density functional theory are carried out, taking into account the core-hole effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
19
0
2
Order By: Relevance
“…Mogi et al (2004) and Tatsumi et al (2005) reported similar calculations, and found that the experimental chemical shifts are reproduced using an allelectron method. The calculated spectra in the present method are compared with experiments in Fig.…”
Section: Elnes Calculation With the Pseudopotential Methodssupporting
confidence: 64%
“…Mogi et al (2004) and Tatsumi et al (2005) reported similar calculations, and found that the experimental chemical shifts are reproduced using an allelectron method. The calculated spectra in the present method are compared with experiments in Fig.…”
Section: Elnes Calculation With the Pseudopotential Methodssupporting
confidence: 64%
“…38 XANES calculations were performed at the Al K-edge for the aqueous octahedral Al 3+ , α-Al 2 O 3 , aqueous tetrahedral Al-(OH) 4 − , and tetrahedral sodium aluminate (NaAlO 2 ) systems, respectively. Previous studies of the Al K-edge XANES have used a plane-wave pseudopotential method 39,40 for Al, AlN, and α-Al 2 O 3 , and studies of aqueous Al(H 2 O) 6 3+ clusters using both "transition state" DFT 41 and a discrete variational (DV) molecular orbital methods. 42,43 In all the ΔSCF and XANES calculations the Sapporo-QZP-2012 all electron basis set 44 was used for the single absorbing Al site, whereas the surrounding O and H atoms were treated with the 6-311G** basis set 45 and the Stuttgart RLC ECPs 46 were used to treat the surrounding Al atoms in the solid-state α-Al 2 O 3 , and tetrahedral sodium aluminate systems, respectively.…”
mentioning
confidence: 99%
“…6c,d, respectively, exhibit temperature-dependent changes. It is noted that Al doped in amber glasses are mostly in the metallic state as featured by a peak at 1560 eV 29,31 , and that the metallic Al peak intensity decreases as temperature increases. Interestingly, the Al 0 peak (represented by the dashed line in Fig.…”
Section: Resultsmentioning
confidence: 99%